Tinjauan Nilai dan Konsep Konservasi Hutan Mangrove di Desa Tanjung Rejo (Wisata Hutan Mangrove Mekar Bahari) - Rizki Amelia Nasution; Zahratul Idami (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
Mangrove forest is one of the natural resources that has the potential for protection and conservation of nature. Conservation can be defined as a system of management and sustainable use of the environment and natural resources. Tanjung Rejo Village, Percut Sei Tuan sub-district is one of the coastal areas with mangrove forest conditions that have been damaged. This study aims to identify the conservation efforts carried out by the people of Tanjung Rejo Village, precisely in the tourist area of the Mekar Bahari Mangrove Forest. The research was conducted by means of surveys, observations and interviews with the management community. The results show that the conservation efforts carried out by protecting and culturing mangrove plants and making mangrove forests as ecotourism and education of mangrove forests have not getting reached for maximum, if viewed from the presence of mangrove plants and the surrounding environment. Based on surveys and interviews about community perceptions of eco-edutourism development, the community agrees that in the near of future the mangrove forest in Tanjung Sari Village will be used as an eco-edutourism area. It can be said that conservation efforts do not reach the standard, so it is important to develop eco-tourism areas in mangrove forests by increasing public awareness ofÂ Â mangrove preservation.Â Keywords: Conservation, eco-edutourism, Mangrove Forest